Climate Change and Fisheries: Meta-Synthesis of Regional Vulnerabilities and Responses - Rekarti, Endi; Wibowo, Martino; Mubarok, Faizul; Klimko, Roman (Lembaga Ketahanan Nasional Republik Indonesia, 2025)
Purpose: This study aims to evaluate the influence of climate change on the viability of the fishing industry across Asia, Oceania, Africa, and the Americas, with particular attention to Indonesia’s fisheries sector. Study Design/Methodology/Approach: The research applies Wavelet Fisher-Z Meta Analysis to 25 peer-reviewed studies published between 2016 and 2024. This method enables the identification of temporal patterns and regional variations in climate impacts on fisheries by stabilising effect size estimates across different environmental and institutional contexts. Findings: The analysis reveals significant impacts of climate change on fisheries in countries including the United States, Colombia, and Vietnam, while moderate effects are observed in Indonesia. The study confirms that elevated sea surface temperatures, erratic weather patterns, and sea-level rise reduce fisheries’ productivity and threaten economic sustainability, particularly in small-scale fishing communities. Originality/Value: This study highlights the urgency of strengthening policy integration, stakeholder coordination, and adaptive capacity in the fisheries sector. It recommends enhancing sustainable fishing practices, establishing marine conservation areas, and investing in infrastructure resilience to withstand climate variability. These findings contribute to ongoing efforts to align national strategies with the Sustainable Development Goals in securing food systems and economic stability.